High temperature and high pressure gas cell for quantitative spectroscopic measurements. (January 2016) - Christiansen, Caspar; Stolberg-Rohr, Thomine; Fateev, Alexander; Clausen, Sønnik
Abstract: A high temperature and high pressure gas cell (HTPGC) has been manufactured for quantitative spectroscopic measurements in the pressure range 1–200 bar and temperature range 300–1300 K. In the present work the cell was employed at up to 100 bar and 1000 K, and measured absorption coefficients of a CO2 –N2 mixture at 100 bar and 1000 K are revealed for the first time, exceeding the high temperature and pressure combinations previously reported. This paper discusses the design considerations involved in the construction of the cell and presents validation measurements compared against simulated spectra, as well as published experimental data. Highlights: A ceramic gas cell designed for gas measurements up to 1300 K and 200 bar. The first recorded absorption spectrum of CO2 at 1000 K and 101 bar is presented. Voigt profiles might suffice in the modeling of radiation from CO2 in combustion.